Recent Advances in Wide-Bandgap Organic–Inorganic Halide Perovskite Solar Cells and Tandem Application - Ting Nie; Zhimin Fang; Xiaodong Ren; Yuwei Duan; Shengzhong (Frank) Liu (Nano-Micro Letters, 2023)
Highlights Wide-bandgap perovskite solar cells are reviewed in detail from the views of compositions, additives, charge transport layers, interfaces and preparation methods. The key factors affecting open-circuit voltage and photostability are carefully discussed. The future directions and challenges in developing wide-bandgap perovskite solar cells are highlighted.